A Divergent Paired Electrochemical Process for the Conversion of Furfural Using a Divided‐Cell Flow Microreactor - Cao, Yiran (ChemSusChem, 2020)
Furfural is a prominent, non‐petroleum‐based chemical feedstock material, derived from abundantly available hemicellulose. Hence, its derivatization into other useful biobased chemicals is a subject of high interest in contemporary academic and industrial research activities. While most strategies to convert furfural require energy‐intensive reaction routes, the use of electrochemical activation allows to provide a sustainable and green alternative. Herein, a disparate approach for the conversion of furfural is reported based on a divergent paired electrochemical conversion, enabling the simultaneous production of 2(5H)‐furanone via an anodic oxidation, and the generation of furfuryl alcohol and/or hydrofuroin via a cathodic reduction. Using water as solvent and NaBr as supporting electrolyte and electron‐mediator, a green and sustainable process was developed, which maximizes productive use of electricity and minimizes byproduct formation.